EFEKTIVITAS TEKNIK RESTRUKTURISASI KOGNITIF UNTUK MENURUNKAN KECEMASAN SOSIAL SISWA SMP - Viana Eka Apriliya; Weni Kurnia Rahmawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Social anxiety is common among junior high school students during early adolescence, a phase highly sensitive to social judgment, and can hinder academic, social, and emotional development. This study examined the effectiveness of cognitive restructuring, a Cognitive Behavioral Therapy (CBT) technique, in reducing social anxiety among junior high school students, using a quasi-experimental pre-test post-test control group design with 13 eighth-grade students (seven experimental, six control) selected through purposive sampling. Data were collected using an adapted Social Anxiety Scale for Adolescents (SAS-A) and analyzed with paired sample and independent sample t-tests. Results showed a significant decrease in the experimental group's social anxiety score (178.43 → 166.71; p = 0.028), while the control group showed no significant change (p = 1.000), with a significant between-group difference in gain scores (p = 0.032; Cohen’s d = 1.369). Cognitive restructuring proved effective and can be recommended for school guidance and counseling services.Keywords: cognitive restructuring; social anxiety; junior high school students; Cognitive Behavioral TherapySocial anxiety is common among junior high school students during early adolescence, a phase highly sensitive to social judgment, and can hinder academic, social, and emotional development. This study examined the effectiveness of cognitive restructuring, a Cognitive Behavioral Therapy (CBT) technique, in reducing social anxiety among junior high school students, using a quasi-experimental pre-test post-test control group design with 13 eighth-grade students (seven experimental, six control) selected through purposive sampling. Data were collected using an adapted Social Anxiety Scale for Adolescents (SAS-A) and analyzed with paired sample and independent sample t-tests. Results showed a significant decrease in the experimental group's social anxiety score (178.43 → 166.71; p = 0.028), while the control group showed no significant change (p = 1.000), with a significant between-group difference in gain scores (p = 0.032; Cohen’s d = 1.369). Cognitive restructuring proved effective and can be recommended for school guidance and counseling services.